Review Article: Tumor Markers, Types and Clinical Applications - RANA; Salah Mohammed Fezea; ameelah Kadhim TAHER ALISAWI (Academic Science Journal)
Over the past ten years, tumor markers have played an increasingly important role in clinical oncology. This trend is expected to continue as technology advances and our knowledge of the human body and disease processes grows. In the treatment of cancer, tumor markers are widely used for a variety of purposes, including screening, selecting a management strategy, determining the prognosis, and post-therapy follow-up. A comprehensive of the fundamentals of pathophysiology and identification strategies for each specific malignancy is necessary for their prudent application in clinical practice. Oncology's use of cancer biomarkers has transformed the way that cancer is treated, and led to notable improvements in patient outcomes and cancer treatment.